Status and practices of digitisation in Kuwaiti academic libraries - Alghnimi, Maali; Chaudhry, Abdus Sattar (Malaysian Journal of Library and Information Science, 2022)
Digitisation offers many advantages for academic libraries. This study explores the status and practices of digitisation in Kuwaiti academic libraries, and librarians’ perceived importance of digitisation. The survey method was employed, and a questionnaire was used to collect data from four universities and two other higher education institutions; one academic institution did not participate due to administrative procedural requirements. All professional librarians from these institutions were invited to participate, 81 responses (65%) were received. The results demonstrated that current digitisation projects focus most on digitising magazines, books, periodicals, dissertations and theses, photographs, and university publications. The respondents reported a moderate level of satisfaction with digitisation projects and attached a high level of importance to starting digitisation projects. This might reflect a high level of awareness among librarians regarding the challenges encountered and their potential solutions. Copyright issues, staff training, and funding were among the top five challenges and suggestions for improving digitisation projects. Several recommendations were suggested based on the results obtained to enhance digitisation in Kuwaiti academic libraries, such as more effort on the part of academic libraries into planning digitisation projects.